The essence of measurement / Alan S. Morris - Morris, Alan S. 1948- (Essence of engineering, 1996)
Presents the subject of instrumentation and its use within measurement systems. The text gives an integrated treatment of systematic and random errors, statistical data analysis and calibration procedures, and discusses such developments as the use of fibre optics and instrumentation networks.